A Decade of Online Advertising Research: What We Learned and What We Need to Know. Issue 1 (1st January 2019) - Liu-Thompkins, Yuping
Abstract : Since the appearance of the first banner ad, online advertising has evolved significantly and now accounts for a substantial portion of all advertising spending. As online advertising tools proliferate, academic research in this area has also matured over time. To capture these developments, this article offers a synthesis of more than 300 articles on online advertising published in major advertising and marketing journals over the past 10 years. The key literature is summarized around six themes: (1) online advertising effectiveness; (2) online advertising mechanisms; (3) creative elements in online advertising; (4) the role of context in online advertising; (5) online personalization; and (6) search advertising. Knowledge gaps in existing research are identified, and important future research questions are suggested.